High‐Voltage Charging‐Induced Strain, Heterogeneity, and Micro‐Cracks in Secondary Particles of a Nickel‐Rich Layered Cathode Material. (7th March 2019) - Mao, Yuwei; Wang, Xuelong; Xia, Sihao; Zhang, Kai; Wei, Chenxi; Bak, Seongmin; Shadike, Zulipiya; Liu, Xuejun; Yang, Yang; Xu, Rong; Pianetta, Piero; Ermon, Stefano; et al.
Abstract: Nickel‐rich layered materials LiNi1‐x‐y Mnx Coy O2 are promising candidates for high‐energy‐density lithium‐ion battery cathodes. Unfortunately, they suffer from capacity fading upon cycling, especially with high‐voltage charging. It is critical to have a mechanistic understanding of such fade. Herein, synchrotron‐based techniques (including scattering, spectroscopy, and microcopy) and finite element analysis are utilized to understand the LiNi0.6 Mn0.2 Co0.2 O2 material from structural, chemical, morphological, and mechanical points of view. The lattice structural changes are shown to be relatively reversible during cycling, even when 4.9 V charging is applied. However, local disorder and strain are induced by high‐voltage charging. Nano‐resolution 3D transmission X‐ray microscopy data analyzed by machine learning methodology reveal that high‐voltage charging induced significant oxidation state inhomogeneities in the cycled particles. Regions at the surface have a rock salt–type structure with lower oxidation state and build up the impedance, while regions with higher oxidization state are scattered in the bulk and are likely deactivated during cycling. In addition, the development of micro‐cracks is highly dependent on the pristine state morphology and cycling conditions. Hollow particles seem to be more robust against stress‐induced cracks than the solid ones, suggesting that morphology engineering can be effective in mitigating the crack problem in these materials. Abstract : Significant oxidation state inhomogeneities induced by high‐voltage charging are revealed for Ni‐rich Li ion battery cathode material by the machine‐learning methodology data analysis of nano‐resolution 3D transmission X‐ray microscopy. The formation and propagation of micro‐cracks are proven to be dependent on the morphology of secondary particles and cycling conditions.